Pressure and pressure derivative analysis for long naturally fractured reservoirs using the tds technique (2010)
Normally, in a heterogeneous formation, the transition period of flow from fissures to matrix takes place during the radial flow regime. However, depending upon the value of the interporosity flow parameter, this transition period can show up before or after the radial flow regime. An accurate understanding of how the reservoir produces and the magnitude of producible reserves can lead to competent decisions and adequate reservoir management. So far, no methodology for interpretation of pressure tests under the above mentioned conditions has been presented. Currently, an interpretation study can only be achieved by nonlinear regression analysis (simulation) which is obviously related to nonunique solutions. Therefore, in this paper, a detailed analysis of pressure and pressure derivative behavior for a vertical well in an elongated closed heterogeneous formation is presented. We studied independently each flow regime, especially the dual-linear flow regime since it is the most characteristic “fingerprint” of these systems; new equations to characterize such reservoirs is introduced and were successfully verified by interpreting both field and synthetic pressure tests for oil reservoirs.